A Comparative Analysis of Mitogenomes in Species of the Tapinoma nigerrimum Complex and Other Species of the Genus Tapinoma (Formicidae, Dolichoderinae) - Areli Ruiz-Mena; Pablo Mora; José M. Rico-Porras; Bernard Kaufmann; Bernhard Seifert; Teresa Palomeque; Pedro Lorite (Insects)
Using next-generation sequencing data, the complete mitogenomes of six species from the genus Tapinoma were assembled. This study explores the mitochondrial genomes of Tapinoma species, among them the five species from the Tapinoma nigerrimum complex, comparing them with each other and with other species from Dolichoderinae subfamily to understand their evolutionary relationships and evolution. Tapinoma mitochondrial genomes contain the typical set of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNAs, and the A + T-rich control region. A phylogenetic analysis using the protein-coding gene sequences from available Dolichoderinae mitogenomes supports the monophyletic nature of the genus Tapinoma, with the T. nigerrimum complex forming a well-supported clade. Key findings include genetic traits unique to the T. nigerrimum complex, such as a start codon in the atp8 gene and a complete stop codon in cox1, distinguishing them from other Tapinoma species. Additionally, a gene rearrangement involving tRNA-Trp, tRNA-Cys, and tRNA-Tyr was found exclusively in the Tapinoma species, suggesting a potential phylogenetic marker for the genus.